Determination Shelf Life and PAHs Content of Smoked Anchovy (Engraulis encrasicolus, Linneaus, 1758) Nugget with Different Level Liquid Smoke Flavors during Chilled Storage - Alcicek, Zayde (Medwell Online, 2011)
This study evaluates the effect of different liquid smoking flavor solution on the shelf life of liquid smoked anchovy nuggets stored at 4 degrees C. The fish were smoked in solutions of 0.4 and 0.7 mL with and without frying and then stored at 4 degrees C. TVB-N, TVC and PVC showed increases with the storage time. As a consequence, the succession of these process, it has been determined that the liquid smoked anchovy nugget can be stored safely under chilled storage for 18 days and 0.7 mL solution and pre-cooking for nuggets was found to be optimal for this product.
Keywords: Anchovy; nugget; liquid smoke flavoring; shelf life; socioeconomic; Turkey